The Significance of The Cat as a Character with Moral Ambiguity in Neil Gaiman's Coraline - Azzahra, Namira; Jatmiko, Rahmawan (Universitas Gadjah Mada, 2023)
This research analyzes the cat in Coraline as a character with moral ambiguity in children’s literature. This study used new criticism theory, focusing on the formal elements which are the plot of the story and the cat’s character and its characterization to analyze the cat’s role and its significance towards Coraline. By applying Janet Burroway’s character presentation methods, this research aims to analyze how the cat with moral ambiguity influenced Coraline in deciding her decisions and choice. This research also discusses the relationship between the cat with Coraline in order to know how deep Coraline’s trust towards the cat to know the significance of a character with moral ambiguity and to investigate the cat’s role in the novel by analyzing the plot of the story. The result shows that even though the cat has a bad and annoying attitudes towards Coraline, after she met the cat and having several conversations, there is a change in her mind about the point of view of the Other World so she could decide what to do in order to save not only herself but also the cat, her parents and the ghost children’s souls from the Beldam. The existence of a character with moral ambiguity is unusual in children’s literature which mostly have obvious narratives about polarity; nevertheless, the cat’s presence in Coraline has a significant role because not only guiding Coraline but also an illustration of not every people with bad attitude is an evil people; even though the cat has moral ambiguity in its character it accommodated Coraline in escaping from the Beldam.